Know to value, intervene and protect. University extension and heritage (Cuadernos de Extensión Universitaria de la UNLPam, 2019)
This article addresses the link between extension and heritage, based on experiences that emerged from University Extension Projects (PEU/UEP). In the first section some aspects of the joint work involved in extension are mentioned. In the second, the relationship between culture and heritage is considered as constitutive aspects of the identity of a society. The third focuses on the preservation of heritage as a cultural right inherent in citizenship. In the fourth, the actions carried out by the Universidad Nacional de La Pampa (National University of La Pampa) in this area are explained.
Keywords: University extension; heritage; identity